Один класс гибридных интегральных преобразований (Бесселя - Фурье - Бесселя - ... - Фурье - Бесселя) на полярной оси с 2n точками сопряжения - Ленюк, М.П.; Олейник, Н.П. (Український математичний журнал, 1993)
The hybrid integral transformations (Bessel-Fourier-Bessel-...-Fourier-Bessel) are constructed on the polar axis with 2n junction points by using the method of a delta-shaped sequence regarded as a Dirichlet kernel. The principal identity of the integral transformation of a differential operator is obtained.